2014
DOI: 10.1039/c4sm01284d
|View full text |Cite
|
Sign up to set email alerts
|

Precision Marangoni-driven patterning

Abstract: A Marangoni flow is shown to occur when a polymer film possessing a spatially-defined surface energy pattern is heated above its glass transition to the liquid state. This can be harnessed to rapidly manufacture polymer films possessing prescribed height profiles. To quantify and verify this phenomenon, a model is described here which accurately predicts the formation, growth, and eventual dissipation of topographical features. The model predictions, based on numerical solutions of equations governing thin fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(61 citation statements)
references
References 34 publications
2
58
1
Order By: Relevance
“…Perturbations can be created atop a polymer film, on a mesoscopic length-scale in a variety of ways. Unfavourable wetting properties [33][34][35][36][37], electrohydrodynamic instability [38][39][40], Marangoni flow [41][42][43][44], and thermocapillary forces [45][46][47][48][49] can all drive a flat film away from a uniform film thickness. The film viscosity η, surface tension γ, and unperturbed film thickness h 0 , are three parameters that influence the effective mobility of a film, which affects the relaxation of an applied surface perturbation.…”
Section: Introductionmentioning
confidence: 99%
“…Perturbations can be created atop a polymer film, on a mesoscopic length-scale in a variety of ways. Unfavourable wetting properties [33][34][35][36][37], electrohydrodynamic instability [38][39][40], Marangoni flow [41][42][43][44], and thermocapillary forces [45][46][47][48][49] can all drive a flat film away from a uniform film thickness. The film viscosity η, surface tension γ, and unperturbed film thickness h 0 , are three parameters that influence the effective mobility of a film, which affects the relaxation of an applied surface perturbation.…”
Section: Introductionmentioning
confidence: 99%
“…The bidirectional flow of the polymer film materials here is driven by melt-state surface tension gradients caused by photochemically imposed chemical patterns. The magnitude of variations in surface tension needed to cause Marangoni flow is extremely small 24 and is potentially below the uncertainty associated with conventional surface energy analysis from water contact angle or pendant drop measurements. To verify the surface tension changes beyond uncertainty, host polymer films subjected to both chemical transformations were dewetted from the top of a hydrophobic surface, and the contact angles of the vitrified droplets were measured using AFM.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…Dehydrogenation of 6% of the repeat units in PS homopolymer results in a surface energy increase of 0.2 dyn/cm at 150°C. 24 This value enabled prediction of the surface energy change for the dehydrogenated styrene−acrylic acid copolymer used in this work.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It is confirmed that the surface tension gradient should be the primary factor, and the other physical changes inside the film are negligible in our system. A small change in the surface tension can cause large mass convection in polymer films 39 . Hence, the surface tension gradient should be taken into more consideration in SRG studies.…”
Section: Srg Film Essentially Without Colourmentioning
confidence: 99%